A Game to Promote Safe Use of Online Media with Mixed Reality Technology - Tannitisataporn, Ganokpan; Nuatongdee, Chanoknet; Jamsri, Pornsuree (My University, 2022)
Currently, online media is widely used and accessible to all ages. Careless use of cooperativeness in online media, however, can allow vulnerabilities that lawbreakers exploit. Learning as much as possible about media also requires users to be engaged and not bored. So, to avoid boring players while learning we offer a mixed reality (MR) technology stimulating game named Catcher. Catcher is a story game whereby players investigate accurate facts from varied evidence in 5 different game levels. By giving a hint of the non-player character (NPC) at the story’s beginning, the player finds clues to add more information toward the conclusion of the complete story. Testing Catcher showed the game can improve systematic thinking skills by 40% and media learning by 64%. By choosing MR technology players can connect directly with the game system. This allows them to effectively learn while having safe fun without being bored.
Keywords: Computational thinking; Gamification; Mixed reality; Online media; Safe cooperative online